Síndrome de Burnout en el personal de Salud del Hospital Julius Doepfner de Zamora - Merino González, María Magdalena (2019)
Burnout Syndrome is a type of work stress observed in health personnel, which affects professional performance. The health staff of the Julius Doepfner Hospital in Zamora, is subjected to permanent stress by direct attention to patients, situation that causes different forms of their behavior, to face these changes that are unknown at the moment. The objective was to know the frequency of Burnout and the possible associated factors in the health personnel of the Hospital. The study was cross-sectional, with a universe of all personnel working in the institution to whom a survey consisting of a sociodemographic part and the Maslach Burnout Inventory questionnaire was applied. The results show emotional exhaustion 9.05%, depersonalization 14.50% and lack of personal fulfillment 25%; which translates the prevalence of Burnout Syndrome of 19.00%; more frequent in men 24.10%. The factors associated with Burnout Syndrome with statistical significance (p <0.05) and strength of association expressed by the OR correspond: excessive work in a frequent way (OR: 12.10), number of working hours per day greater than 53 hours (OR: 4.72), too many tasks frequently (OR: 4.15), occupational activity (OR: 4.03), more than two jobs (OR: 3.10). The doctors had greater predisposition (OR: 4.03) (p: 0.0001). In conclusion, the Burnout Syndrome affects the health personnel of the aforementioned hospital and there is a good percentage of professionals who are at high risk of suffering from it. Key Words: Personal Health, Zamora, Test Maslach Burnout Inventory